Pengaruh Perubahan Arus Kas Yang Dimoderasi Oleh Korelasi Serial Dalam Perubahan Arus Kas Dalam Memprediksi Akrual - Nurjannah Nurjannah; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study was to examine the effect of cash flow change serial correlation in moderating the relationship of cash flow change and accruals. This study is classified as causative research. The population in study are manufacturing companies listed on the Indonesia Stock Exchange of period 2016 to 2018. By using purposive sampling method, there were 43 companies as the research’s sampel. The type of data used is secondary data obtained from the official site of the Indonesia Stock Exchange and company’s official website. Used is panel regression analysis. The result indicate that cash flow changes has negative and siginificant effect on accrual, but cash flow changes serial correlation is not able to strengthen or weaken the relationship between cash flow changes and accrual.